Analisis Persepsi Brand Association Menurut Pelanggan Sabun Mandi Cair Luk Pada PT. Unilever Indonesia, Tbk (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2020)
his study aims to describe the factors that influence consumers' desire to buy Lux liquid bathsoap in the perception of the brand association at PT Unilever Indonesia, Tbk. How is theperception of the brand association according to customers of Lux liquid bath soap at PTUnilever Indonesia, Tbk. The population of this study were customers or buyers of Lux liquidsoap at the Indomaret Gading Raya Minimarket, East Jakarta and because it used theaccidental sampling method, this study obtained 50 respondents at the Indomaret GadingRaya Minimarket, East Jakarta from March 2019 to April 2019. Data collection methods bymeans of field research (field research) by distributing questionnaires and data libraryresearch. The data processing technique used is data processing with the help of SPSS version21 software (validity and reliability tests) and using a Likert scale. The results of the analysisshow that the perception of the brand association according to customers of Lux liquid bathsoap to customers or buyers of Lux liquid soap at the Indomaret Gading Raya Minimarket,East Jakarta is influential.